2018
DOI: 10.3889/oamjms.2018.372
|View full text |Cite
|
Sign up to set email alerts
|

Silencing HCV Replication in Its Reservoir

Abstract: BACKGROUND:HCV infection and its complications are among the leading public health challenges; the emergence of drug-resistant variants are expected to be a major problem. A novel combinatorial small interfering RNA (siRNA) could be a novel triple therapy that could be suitable for genotype 4. Although HCV is a hepatotropic virus, there is reliable evidence about its replication in peripheral blood mononuclear cells (PBMC) of chronically infected patients; these cells act as an extra-hepatic reservoir for vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Hepatitis E is one of five known human hepatitis viruses. Others are A [5], B [6], [7], C [8], [9], [10] and D [11]. The prevalence of HEV is very low compared with the others, especially hepatitis B virus (HBV).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis E is one of five known human hepatitis viruses. Others are A [5], B [6], [7], C [8], [9], [10] and D [11]. The prevalence of HEV is very low compared with the others, especially hepatitis B virus (HBV).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have clearly showed that, as in the case of HIV, the simultaneously expression of more than one RNAi sequences is more efficient in blocking viral replication as well as in preventing escape mutations [ 57 , 58 ]. In this context, the simultaneous targeting of viral and host factors involved in viral replication represents a successful strategy in terms of both antiviral effect and prevention of viral mutant selection [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RNAi might represent a promising therapeutic tool against HCV as targeting viral genome through specific siRNAs should halt viral replication and propagation. Furthermore, it has been previously demonstrated that not only silencing of viral factors, but also interfering with cellular proteins known to play a role in HCV life cycle, would block viral replication [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In particular, it has been shown that combinatorial strategies based on the co-expression of arrays of siRNAs targeting multiple viral and/or cellular genes displayed synergistic anti-HCV effects, hence reducing the possibility of resistant variant emergence [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 Continuous treatment with one RNAi molecule could encourage the appearance of several point mutations located inside the specific viral region. 24 To overcome developing viral mutations, multiple RNAi molecules aiming at multiple regions of the HCV genome is recommended, in addition to siRNAs against cellular proteins involved in HCV replication. The value of siRNA as a therapy against HCV infection will depend on establishing effective delivery systems that achieve a long-lasting RNAi activity.…”
Section: Discussionmentioning
confidence: 99%